The Existence Of The Metaverse Tourism In Indonesia: Between Opportunities And Threats - Putra, Dyan Triana; Mahmudin, Tono; Wiartha, Nyoman Gede Mas; Adnyana, I Made Sucipta; Septiviari, A. A. Istri M. (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to determine (1) the opportunities and threats of the existence of the metaverse for tourism in Indonesia; and (2) strategy for developing Indonesian tourism through the metaverse. This research is descriptive qualitative research. This research uses a SWOT analysis regarding the existence of the metaverse for Indonesian tourism. The results of this research show that (1) the existence of metaverse tourism related to tourism experiences has the opportunity to make tourist trips more interactive and becomes a threat because it is considered less than optimal, while related to technology (internet access) the existence of metaverse tourism has the opportunity to become an innovation in tourism trends and become a threat because it is not evenly distributed internet access in Indonesia, and related to health, the existence of metaverse tourism has the opportunity to be a solution for people with disabilities because it can be long distances and is a threat due to radiation problems; and (2) Indonesian tourism development strategy based on SWOT analysis consisting of SO strategy through marketing planning for metaverse tourism as a current tourism trend, WO strategy through socializing the use of metaverse in Indonesian tourism by developing a metaverse tourism concept for tourists, ST strategy through collaboration with the Tourism Office and the private sector supports metaverse tourism, and WT strategies through education and promotion of metaverse tourism programs.